PTU-137 The hospital admission burden of coeliac disease: a 12 year retrospective analysis from a district general hospital. (17th June 2017) - Patel, J; Bhuva, M; Sakthivel, GD; Rostami, K; Marsh, MN; Johnson, MW
Abstract : Introduction: Due to financial pressures within the NHS, many CCG's have recently decommissioned gluten-free prescriptions for coeliac disease (CD) patients. Unfortunately, the true financial impact of coeliac disease on the NHS, has never been fully understood. In order to protect the care of CD patients in our local catchment, we sort to understand the existing burden of care of these patients, particularly on the hospital admission system, through daycase procedures and direct inpatient stay. Method: The Luton and Dunstable University Hospital has a database of 1317 patients with coeliac disease [Male n=467, Female n=850; Age range: 1–102 years old; mean age 58; current paediatric patients (age ≤16) n=61]. Using this database for reference, the hospital coding system was used to analyse the total number of inpatient (stay) and day-case admissions between 2005–2016, and identify the admitting specialties. Results: For the 1317 coeliac patients, there were 1267 inpatient admissions. The number of inpatient admissions per patient (all ages) ranged from 0–51. The length of inpatient stay ranged from 1–64 days, with a total 5018 days spent within hospital, at an average 3.96 days per inpatient stay. Patients were admitted under a range of different specialities; general medicine n=556; paediatrics n=384; general surgery n=181; trauma and orthopaedics n=76; Obstetrics and Gynaecology (O and G) n=35; ear, nose and throat n=13; maxillofacial surgery n=13; urology n=9. There were 698 daycases involving the CD patients: the top 3 ranking specialties included dermatology n=124; O and G n=91, and ophthalmology n=88. Conclusion: A total 1965 hospital admissions were attained by CD patients over 12 years (163.75 admissions/year), accounting for a total 5716 days spent within the hospital setting. On average, each patient had a mean of 1.49 hospital admissions. In total, 30% of all the CD inpatient admissions were seen in paediatric patients, highlighting its importance in the health of these younger patients. A surprisingly high number of cataract operations (74) were performed in these CD patients (independent of age) raising the possibility of a link. 24 miscarriages and 2 ectopic pregnancies were also documented, suggesting that CD may have a more important role in fertility and fecundity than previously thought. The role of coeliac disease within fertility may be underestimated. Not all the hospital admissions were directly related to underlying coeliac disease, but there clearly appears to be an increased demand placed on the local hospital admission services from these patients. Disclosure of Interest: None Declared